Microbiological and physicochemical characterization of organic and nonorganic honey sold in São Paulo State - SAMPAIO, Aryele Nunes da Cruz Encide; CHINAQUE, Layara Chuvukian; PESCINELLI, Ana Carolina Gaspar; CARON, Evelyn Fernanda Flores; CÉZAR, Camila Koutsodontis Cerqueira; POSSEBON, Fabio Sossai; PEREIRA, Juliano Gonçalves; MARTINS, Otávio Augusto (Food Science and Technology, 2024)
This study assesses the microbiological and physicochemical quality of organic and nonorganic honey sold in São Paulo State, Brazil. A total of 26 samples were analyzed, 10 samples of organic honey (OH) and 16 of non-organic honey (NOH) sold in São Paulo State, Brazil. Physicochemical analyses revealed notable variations in moisture, acidity, and hydroxymethylfurfural (HMF) levels between OH and NOH. The average moisture content was 17.74 ± 1.47 g/100 g for OH and 18.12 ± 1.73 g/100 g for NOH. Regarding acidity, OH had an average of 26.90 ± 14.58 mEq/kg, while NOH had 34.32 ± 11.22 mEq/kg. Regarding HMF, OH had an average of 23.40 ± 38.70 mg/kg and NOH had 35.82 ± 39.94 mg/kg. Samples showing deviations from legal standards indicate potential processing or storage issues. The Fiehe test indicated possible fraud in one OH sample and four NOH samples. The Lund test showed no precipitation in any samples, suggesting adulteration in all of them. Diastatic enzyme research revealed the absence of enzymes in three samples, indicating adulteration or inadequate processing. The mean counts of mesophiles were 23 CFU/g for OH and 55.33 CFU/g for NOH, while the counts of molds and yeasts were 126.5 CFU/g for OH and 2289 CFU/g for NOH, exceeding recommended limits and raising concerns about product safety. These findings underscore the need for rigorous quality control measures throughout honey production to ensure safety, purity, and authenticity.